Infant milk formulas differ regarding their allergenic activity and induction of T‐cell and cytokine responses. Issue 3 (18th September 2016) - Hochwallner, H.; Schulmeister, U.; Swoboda, I.; Focke‐Tejkl, M.; Reininger, R.; Civaj, V.; Campana, R.; Thalhamer, J.; Scheiblhofer, S.; Balic, N.; Horak, F.; Ollert, M.; et al.
Abstract: Background: Several hydrolyzed cow's milk (CM) formulas are available for avoidance of allergic reactions in CM‐allergic children and for prevention of allergy development in high‐risk infants. Our aim was to compare CM formulas regarding the presence of immunoreactive CM components, IgE reactivity, allergenic activity, ability to induce T‐cell proliferation, and cytokine secretion. Methods: A blinded analysis of eight CM formulas, one nonhydrolyzed, two partially hydrolyzed (PH), four extensively hydrolyzed (EH), and one amino acid formula, using biochemical techniques and specific antibody probes was conducted. IgE reactivity and allergenic activity of the formulas were tested with sera from CM‐allergic patients ( n = 26) in RAST‐based assays and with rat basophils transfected with the human FcεRI, respectively. The induction of T‐cell proliferation and the secretion of cytokines in Peripheral blood mononuclear cell (PBMC) culture from CM allergic patients and nonallergic individuals were assessed. Results: Immune‐reactive α‐lactalbumin and β‐lactoglobulin were found in the two PH formulas and casein components in one of the EH formulas. One PH formula and the EH formula containing casein components showed remaining IgE reactivity, whereas the other hydrolyzed formulas lacked IgE reactivity. Only two EH formulas and the amino acid formula did not induce T‐cell proliferation and proinflammatory cytokine release. The remaining formulas varied regarding the induction of Th2, Th1, and proinflammatory cytokines. Conclusion: Our results show that certain CM formulas without allergenic and low proinflammatory properties can be identified and they may also explain different outcomes obtained in clinical studies using CM formulas.